A facile and sustainable approach for simultaneously flame retarded, UV protective and reinforced poly(lactic acid) composites using fully bio-based complexing couples. (15th June 2021) - Zhou, Yuyang; Tawiah, Benjamin; Noor, Nuruzzaman; Zhang, Zheng; Sun, Jun; Yuen, Richard K.K.; Fei, Bin
Abstract: The integration of bio-based functional agents with biopolymers is welcomed as a way of meeting the growing demand for healthy, safety, and sustainability. This study presents a facile and solvent-free fabrication of flame retardant (FR), UV protective, and reinforced poly(lactic acid) (PLA) composite using two bio-based complexing couples: tannin acid/ferric salt (TAFe) and chitosan/phytic acid (CTSPA). The thermal and burning properties of PLA composites were evaluated by thermogravimetric analysis (TGA), limited oxygen index (LOI), UL-94 test, and cone calorimetry. The UV protective and tensile properties were also evaluated. PLA/TAFe and PLA/CTSPA showed earlier mass loss and higher char residue than pristine PLA. CTSPA (3 wt%) enhanced the LOI value of PLA from 19.6% to 30.5%. PLA/CTSPA and PLA/TAFe/CTSPA achieved V-0 ratings in UL-94 test with slight melt dripping. Cone calorimetry demonstrated that 2.5 wt% apiece of TAFe and CTSPA led to obvious reductions in peak heat release rate and total heat release. Interestingly, the combination of TAFe and CTSPA was effective in suppressing CO production. PLA/TAFe had a higher UPF value (50+) and tensile strength than pristine PLA. In conclusion, the sustainable strategy developed in this study represents the concept of fabricating fully bio-based polymer composites via a solvent-free process, which can also be generalized into the eco-design for other multifunctional polymer systems. Graphical abstract: Image 1 Highlights: Simultaneously flame retarded, UV protective and reinforced PLA was fabricated. Bio-based couples significantly enhanced the LOI value of PLA to 30.5%. Flame retarded PLA composites achieved a V-0 rating in the UL-94 test. Bio-based couples greatly reduced total heat release and CO production of PLA. PLA/bio-based couple composites had a UPF value higher than 50.